MCM-41 support for ultrasmall γ-Fe2O3 nanoparticles for H2S removal. Issue 41 (26th July 2017) - Cara, C.; Rombi, E.; Musinu, A.; Mameli, V.; Ardu, A.; Sanna Angotzi, M.; Atzori, L.; Niznansky, D.; Xin, H. L.; Cannas, C.
Abstract : MCM-41 is proposed to build mesostructured γ-Fe2 O3 -based sorbents as an alternative to other silica or alumina supports for mid-temperature H2 S removal. Abstract : MCM-41 is proposed to build mesostructured Fe2 O3 -based sorbents as an alternative to other silica or alumina supports for mid-temperature H2 S removal. MCM-41 was synthesized as micrometric (MCM41_M) and nanometric (MCM41_N) particles and impregnated through an efficient two-solvent (hexane–water) procedure to obtain the corresponding γ-Fe2 O3 @MCM-41 composites. The active phase is homogeneously dispersed within the 2 nm channels in the form of ultrasmall maghemite nanoparticles assuring a high active phase reactivity. The final micrometric (Fe_MCM41_M) and nanometric (Fe_MCM41_N) composites were tested as sorbents for hydrogen sulphide removal at 300 °C and the results were compared with a reference sorbent (commercial unsupported ZnO) and an analogous silica-based sorbent (Fe_SBA15). MCM-41 based sorbents, having the highest surface areas, showed superior performances that were retained after the first sulphidation cycle. Specifically, the micrometric sorbent (Fe_MCM41_M) showed a higher SRC value than the nanometric one (Fe_MCM41_N), due to the low stability of the nanosized particles over time caused by their high reactivity. Furthermore, the low regeneration temperature (300–350 °C), besides the high removal capacity, renders MCM41-based systems an alternative class of regenerable sorbents for thermally efficient cleaning up processes in Integrated Gasification Combined Cycles (IGCC) systems.